FIGURE OF SPEECH ON THE SONGS IN THE ALBUM GAJAH BY TULUS - Nadia Aurelia Dea Safira; Tris Trismanto (Universitas 17 Agustus 1945 Semarang, 2022)
The topic of this research is the use of figure of speech in three song lyrics. The title of this research is